1995
DOI: 10.1111/j.1472-765x.1995.tb00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of plasmid profiling as a typing method for epidemiologically related Clostridium perfringens isolates from food poisoning cases and outbreaks

Abstract: Plasmid profiling was used for the characterization of Clostridium perfringens isolates involved in disease outbreaks. The usefulness of this technique was demonstrated by the retrospective examination of food and patient isolates from 10 cases and outbreaks from 1984 to 1991. The origin of three outbreaks could be clearly confirmed due to identical plasmid profiles in all isolates. In one outbreak identical plasmid patterns were found between one food and one patient isolates, while one plasmid was missing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Currently, costs and accessibility also remain problematic. A recent comparison of multiple genomes of strains of the same species has shown that considerable gene variation exists within a species, and the term 'pan genome' was coined to denote the cumulative genome deduced from the individual genome sequences [185]. Hence, it is emphasised that analyses based on single-strain genomes of a given species are not likely to be sufficient to make generalisations about the species as a whole.…”
Section: Genome Analysis By Array Hybridisationmentioning
confidence: 99%
“…Currently, costs and accessibility also remain problematic. A recent comparison of multiple genomes of strains of the same species has shown that considerable gene variation exists within a species, and the term 'pan genome' was coined to denote the cumulative genome deduced from the individual genome sequences [185]. Hence, it is emphasised that analyses based on single-strain genomes of a given species are not likely to be sufficient to make generalisations about the species as a whole.…”
Section: Genome Analysis By Array Hybridisationmentioning
confidence: 99%
“…Plasmid typing was the first molecular method to be used as a bacterial typing tool (10,80,164,181,240,273,274,325). Plasmids are self-replicating, often-transferable extrachromosomal DNA elements in the prokaryote cytoplasm.…”
Section: Plasmid Analysismentioning
confidence: 99%
“…Many genotypic methods, including plasmid analysis (14,24,35), ribotyping (15,34), PCR (7,12,20), pulsed-field gel electrophoresis (PFGE) (10,25,30), and amplified-fragment length polymorphism (27), have already been used, and their discriminatory powers in the study of C. perfringens isolates have been tested. PFGE has been used to study the location of the cpe gene and the isolates associated with non-food-borne human gastrointestinal diseases (10,11,19,37).…”
mentioning
confidence: 99%